Detección del potyvirus johnsongrass mosaic virus en Argentina - Trucco, Veronica Milagros; Cabrera Mederos, Dariel; Castellanos Collazo, Onias; Vaghi Medina, Carlos Gaston; Lenardon, Sergio Luis; Giolitti, Fabian (Asociación Argentina de Fitopatólogos, 2021)
Poster